Making room for the simultaneous use of different rationalities in transport planning: The case of Strategic Choice of Measures in Swedish transport planning - Tornberg, Patrik; Odhage, John (Proceedings from the Annual Transport Conference at Aalborg University, 2017)
Strategic Choice of Measures (SCM) was established in 2013 as an arena for early dialogue between main actors and stakeholders at local, regional and national level to jointly assess transport related problems and develop solutions. This paper explores the presence and use of different rationalities in SCM with the aim to conceptualize its characteristics as a new step in Swedish national transport planning. The analysis of SCM from a rationality perspective is focused on the ways in which SCM makes use of, facilitates and enables different kinds of rationalities in giving reason for decision makers to justify decisions and courses of actions. Three types of rationality have been used in the analysis: Instrumental, communicative and strategic rationality. The official SCM handbook and three cases are interpreted as simultaneously using different rationalities, but the relative weight and dominance of different rationalities vary from case to case, also with regards to connections between rationalities. The paper concludes that SCM is an example of a transport planning approach that has the potential to result in decisions that can be instrumentally, strategically and communicatively rationally motivated. Furthermore, the issue of conditions and context influencing each case is also noted, although not investigated, thus setting an agenda for further research.